2004
DOI: 10.1074/jbc.m313801200
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Phospholipase Cζ Has High Ca2+ Sensitivity and Induces Ca2+ Oscillations in Mouse Eggs

Abstract: ] i rises are a pivotal signal for egg activation and are responsible for early embryogenesis (2, 3). Accumulated evidence suggests that Ca 2ϩ oscillations are induced by cytosolic sperm factor introduced into the ooplasm upon sperm-egg fusion (2, 4). Therefore, the identification of the Ca 2ϩ oscillation-inducing sperm factor, which is the egg-activating sperm factor, is currently being studied as a central subject to elucidate the mechanisms of fertilization. Recently, Saunders et al.(5) have reported a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
185
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(203 citation statements)
references
References 28 publications
15
185
1
2
Order By: Relevance
“…We have recently shown (7) that the PI(4,5)P 2 -hydrolyzing activity of recombinant PLC is ϳ100-fold more sensitive to Ca 2ϩ than that of PLC␦1 and is 70% maximal at 100 nM [Ca 2ϩ ], which is usually the basal [Ca 2ϩ ] i of cells. Recombinant PLC has ϳ20-fold higher Ca 2ϩ oscillation-inducing activity than PLC␦1 (7). Thus, PLC possesses remarkable properties that are favorable for the sperm factor to initiate (7) and maintain (3) Ca 2ϩ oscillations via continuously produced IP 3 .…”
Section: Plcmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown (7) that the PI(4,5)P 2 -hydrolyzing activity of recombinant PLC is ϳ100-fold more sensitive to Ca 2ϩ than that of PLC␦1 and is 70% maximal at 100 nM [Ca 2ϩ ], which is usually the basal [Ca 2ϩ ] i of cells. Recombinant PLC has ϳ20-fold higher Ca 2ϩ oscillation-inducing activity than PLC␦1 (7). Thus, PLC possesses remarkable properties that are favorable for the sperm factor to initiate (7) and maintain (3) Ca 2ϩ oscillations via continuously produced IP 3 .…”
Section: Plcmentioning
confidence: 99%
“…Ca 2ϩ oscillations similar to those at fertilization are produced by PLC expressed in a mouse egg at an estimated level comparable with the content in a single mouse sperm (1,2). Injection of recombinant PLC into mouse eggs induces Ca 2ϩ oscillations as well (7). The Ca 2ϩ oscillation-inducing activity of sperm extract (4,8) is lost when the extract is pretreated with an antibody against PLC (1).…”
Section: Plcmentioning
confidence: 99%
“…The sperm-specific PLC-isoform was found to trigger fertilizationlike Ca 2ϩ oscillations in eggs (4). In vitro measurements demonstrated that, although enzymatic activity is lower, PLC-has a 100-fold greater sensitivity to Ca 2ϩ indicating that this isoform is active at Ca 2ϩ concentrations equivalent to those in cells at the resting state (12). Recently, two groups independently cloned novel PLC-isoforms that are activated in a calcium dependent fashion (4,13).…”
mentioning
confidence: 99%
“…A splicing variant of PLC lacking 110 residues from the N terminus corresponding to the EF-hands 1-3 but identical to PLC in EF4 and the succeeding region failed to elicit a Ca 2ϩ spike (36). This indicates that the EF-hand domain is important for PLC to induce Ca 2ϩ oscillations (which presumably requires correct membrane binding).…”
Section: Discussionmentioning
confidence: 92%